The biographical value of identity and memory through sexual dissidence in Esther Tusquets’ Habíamos ganado la Guerra (Anclajes, 2024)
Habíamos ganado la guerra, one of Esther Tusquets’ autobiographical texts, published in 2007, allows us to enrich the question of the representation of homoeroticism in her novels. The sexual dissidence of the character José, one of the first loves of the young Esther, can be understood not only as the recovery of her past, but also as a reflection of the present moment of writing, through the narrative and dramatic strategies chosen in the process of creation. From this perspective, in the light of theoretical studies on autobiography and social-historical studies, it is analysed how the episode in which she narrates her story with José dialogues both with her youthful “me”, in force at the time of the modification of the Ley de Vagos y Maleantes, and with the author who publishes in 2007.
Keywords: Contemporary literature; Autobiography; Francoism; Homosexual; Shame